Seni Perhiasan Pada Masa Kerajaan Majapahit - Ari Supriyanto (Institut Seni Indonesia Surakarta, 2012)
Majapahit was one of the kingdoms in Java from late classical period. Various relics of the Majapahit empire had been found, but the discovery of artifacts in the form of jewelry from the Majapahit kingdom was not much that was rescued by the government. Based on these, encouraging writers to try to write about the jewelry of the kingdom of Majapahit. This short paper is a preliminary study on the headway of jewelry from the Majapahit kingdom, and in connection with the relics of a bygone era then the preparation of this paper comes from many sources related to the history of the kingdom of Majapahit and jewelry produced from that era. Keywords: jewelry, Majapahit kingdom